Effectiveness of the Gamification Method in the Process of Phenomenon-Based Learning in Secondary School (In the Example of Kazakhstan) - N.A, Ermakan; B.S, Ualikhanova; B.K, Rakhashev; S.A., Ramazanova (Journal of Ecohumanism, 2024)
In today’s educational environment, it is essential to introduce innovative methods to increase students’ activity and improve learning results. In this study, a detailed examination of domestic and foreign literature is conducted to analyze gamification’s effectiveness and specific aspects in various educational settings. The main goal of the study is to evaluate the effectiveness of gamification in the educational system of Kazakhstan, paying special attention to the use of gamification in teaching physics. To achieve this goal, mixed methods were used, including qualitative and quantitative analysis. The survey involved 59 randomly selected students of 8 and 10 grades of general education schools in Kazakhstan and studied a set of tasks related to the game in the classroom. The results of the survey showed that gamification is accepted as an effective method in the teaching of physics in the Kazakhstan education system. Pupils’ attitudes towards game-based learning were positive, indicating an improvement in their motivation and engagement levels, as well as an improvement in their understanding of physics. To increase student engagement in STEM subjects, educators should consider incorporating gamification into the curriculum.